Pengaruh Atribut Belanja Online pada Kepuasan dan Loyalitas Pelanggan dari Pengalaman Marketpleace Tokopedia - Basith, Ahmad Ibnul; Sugiyanto, Sugiyanto (Sahabat Publikasi, 2023)
This study aims to determine what factors influence the satisfaction and loyalty of Tokopedia marketplace customers. The variables used in this study are information quality, privacy concerns, perceived security, product variety, product delivery, consumer satisfaction and consumer loyalty. The population in this study are marketplace users who have used and shopped at the Tokopedia marketplace with a sample size of 150 respondents. The data collection technique used a questionnaire, and the data analysis technique used was the SmartPLS 4.0 analysis tool. Based on the results of the study, of the 16 hypotheses there are 10 hypotheses that are accepted, namely information quality, perceived security and product variety have a positive effect on consumer satisfaction. Perceived safety, product variety, and product delivery have a positive effect on consumer loyalty. information quality, perceived security, and product variety have a positive effect on consumer loyalty through consumer satisfaction. The contribution to this research resulted in a model for measuring the effectiveness of the Tokopedia marketplace system that can be used by companies to develop in the future so as to increase user satisfaction at Tokopedia.